2009
DOI: 10.1080/01140670909510256
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of clonal variations in cultivated quince (Cydonia oblonga‘Kalecik’) based on fruit characteristics and SSR markers

Abstract: This study assessed uniformity within a quince cultivar (Cydonia oblonga 'Kalecik'). The fruit traits of six different clones within 'Kalecik' quince plantations were evaluated over a 2-year period. Additionally, clones were genetically analysed at seven SSR (microsatellite) loci (CH01f02, CHOlhOl, CH01h10, CH01d08,CH02b12,KA16, and KA14). According to important fruit characteristics, clone 6 was selected as the best in both years. This clone had a lower fruit skin colour hue value (92.7-88.5°), higher soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 18 publications
(24 reference statements)
1
20
0
1
Order By: Relevance
“…In our study, the H O values were found to be high for CH01F02, CH01H10, CH02B12, KA4b, KA16, and CH04E03 loci (Table 2), and previous reports also found relatively high H O values for CH01F02, CH02B12, and KA16 (Dumanoğlu et al, 2009) and for CH01H10 (Dumanoğlu et al, 2009;Bassil et al, 2011) in some quince cultivars.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…In our study, the H O values were found to be high for CH01F02, CH01H10, CH02B12, KA4b, KA16, and CH04E03 loci (Table 2), and previous reports also found relatively high H O values for CH01F02, CH02B12, and KA16 (Dumanoğlu et al, 2009) and for CH01H10 (Dumanoğlu et al, 2009;Bassil et al, 2011) in some quince cultivars.…”
Section: Discussionsupporting
confidence: 81%
“…SSR markers developed from other Prunus species (apple and pear) were used successfully for the genetic characterization of quince cultivars in this study, as has been observed previously (Dumanoğlu et al, 2009;Halász et al, 2009;Bassil et al, 2011).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations